PELATIHAN DAN PENGEMBANGAN MATERI ROBOTIK DAN PEMROGRAMAN UNTUK ANAK BERKEBUTUHAN KHUSUS - Sebastian, Danny; Restyandito; Nugroho, Justinus Putranto Agung (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2024)
Developing educational modules for children with exceptional needs necessitates comprehensive modifications to accommodate the child's unique intellectual and behavioral requirements. The Individualized Approach prioritizes the customization of materials according to the child's unique abilities and interests. For instance, in a programming module, platforms like Scratch can facilitate the introduction of concepts through a visual and interactive approach that enhances comprehension. In a LEGO module, activities are organized to enable children to assemble components incrementally through visual aids, deconstructing intricate jobs into manageable steps, so minimizing frustration and enhancing progressive comprehension. Structure and routines assist children with behavioral issues in maintaining focus, but a multisensory approach facilitates information processing through the senses. Through task analysis, intricate materials are deconstructed into more manageable elements, facilitating a structured and comprehensible learning experience for youngsters. This amalgamation of methodologies guarantees that educational modules are both successful and inclusive, particularly when employing interactive and enjoyable products like LEGO. Based on observations made during teaching process using the developed materials, children with special needs can maintain focus longer than before using the developed materials. This observation is still limited, so an evaluation needs to be carried out using more standard measurements and a longer period of time. Suggestions for further activities are to develop materials that are specific to the type of special needs.